How clinical problem-based medical education sets the scene for social identity formation in medical students - Nicolaj Johansson (Dansk Universitetspædagogisk Tidsskrift, 2026)
This article examines how clinical problem-based medical education (PBL) shapes medical students’ social identity formation and influences how they learn in clinical practice. Drawing on an ethnographic study comprising 240 hours of observations and eight hours of individual interviews with seven medical students, the analysis identifies three prominent and dynamically shifting identity positions: medical student, nearly physician and colleague. These identities structure how students participate in clinical work, the degree of autonomy they assume and how they interpret their professional responsibilities. Through the lens of social identity theory, the study shows that high-quality learning arises not from a single identity position but from the dynamic balance between them. The findings highlight how identity salience affects deep learning, reflective practice and patient safety, and point to the need for curriculum designs that scaffold progressive autonomy, strengthen inclusive clinical cultures, and integrate structured reflection to prepare students for clinical practice.